Criminological characterization of corruption offenses in the countries of the European Union - A.V. Tkachenko (Економіка, управління та адміністрування)
The publication is dedicated to the criminological analysis of criminal corruption offenses in the European Union as a whole and in individual EU member states, with the aim of drawing conclusions about the effectiveness of anti-corruption policies in European countries. A quantitative analysis of corruption-related crimes registered in EU member states from 2016 to 2021 year has been conducted. Using the examples of Eastern European countries bordering Ukraine that have relatively recently joined the EU (Romania, Poland), as well as Western European countries (France and Portugal), the study examines the prevalence of corruption, its geographical distribution, and the most attractive sectors for the implementation of corruption schemes. The analysis of the outcomes of the European Union’s anti-corruption policies will contribute to improving the reform of Ukraine’s anti-corruption policy in the course of its European integration, taking into account the general requirements of the European Union, on the one hand, and the national economic, legal, social, and security-related specificities, on the other.